COVID-19 PANDEMIC IN THE QURAN LITERATURE (Study of Interpretation Maudhu'i About Thaun in Islam) - Zamakhsyari Abdul Majid (Almarhalah | Jurnal Pendidikan Islam, 2021)
ABSTRACTThis paper aims to identify and analyze Al-Quran literature on the development and problems of the Covid-19 outbreak through the study of Maudu'i Tafsir which is viewed from the substance of Thaun as disease transmission in Islam. This study uses a qualitative-descriptive method by trying to trace various works and writings related to the focus of the study, either directly or indirectly. The works are read carefully and then analyzed and interpreted qualitatively according to the pre-determined study problems. This research is a library research. The results of this paper indicate that viruses, bacteria, germs or similar diseases are created by Allah which has the analogy of being the smallest animal of a mosquito (Fauqo Ba'udhah) and has a contagious and deadly impact. Infectious diseases such as Covid-19 have properties that can be controlled so that they do not fall into damage and destruction (wa la tulqu bi aidikum ila at-tahlukah) the values of human life on earth.Keywords: Pandemic, Covid-19, Thaun, Al-Quran